High‐resolution melting of the cytochrome B gene in fecal DNA: A powerful approach for fox species identification of the Lycalopex genus in Chile. Issue 13 (14th June 2019) - Anabalón, Leonardo; Encina‐Montoya, Francisco; Sánchez, Pamela; Solano, Jaime; Benavente, Felipe; Guiñez, Basilio; Olivares, Flavio; Oberti, Carlos; Vega, Rolando
Abstract: Easy, economic, precise species authentication is currently necessary in many areas of research and diagnosis in molecular biology applied to conservation studies of endangered species. Here, we present a new method for the identification of three fox species of the Lycalopex genus in Chile. We developed an assay based on high‐resolution melt analysis of the mitochondrial cytochrome B gene, allowing a simple, low cost, fast, and accurate species determination. To validate the assay applicability for noninvasive samples, we collected fecal samples in the Atacama Desert, finding unexpectedly one species outside of its known distribution range. We conclude that the assay has a potential to become a valuable tool for a standardized genetic monitoring of the Lycalopex species in Chile. Abstract : The mitochondrial cytochrome B gene DNA barcode coupled with the high‐resolution melting method to foxes taxonomic identification of the genus Lycalopex . This technique recognized the three species of Lycalopex present in Chile.